Drill Based Speaking Skills: A Linguistic Review of Arabic ‎Language Learning - Febriyani, Gita; Mahyudin Ritonga (Journal of Practice Learning and Educational Development, 2026)
Speaking skills is an essential aspect of Arabic language proficiency that directly reflects students' communicative skills. In the context of Arabic language learning, the development of Speaking skills often faces various obstacles, such as a lack of intensive speaking practice and suboptimal learning methods. This study aims to explore the effectiveness of applying the drill method in improving Speaking skills in grade XI students at Madrasah Aliyah Nurul Haq Semurup. This study was designed quantitatively using a quasi-experimental approach, which is a study conducted by comparing the experimental group before and after receiving treatment. The instruments used to obtain data were pre-test and post-test. The population in this study was all 11th grade students at Nurul Haq Semurup Islamic High School in the 2025 academic year, with a sample of 15 students. The data collection techniques were observation, tests, and documentation. Then, the data analysis technique used 4 data tests, namely: normality test, homogeneity test, hypothesis test, and n-gain test. Based on the data analysis, the results of the t-test that had been carried out showed that the significance value (Sig.2-tailed) was 0.000 or less than < 0.05. Based on the above description, it can be concluded that H0 is rejected or H1 is accepted, so that there is a significant effect on the application of the drill method in improving students' s